IMPLEMENTATION OF QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) IN A DIGITAL-BASED PROMOTION STRATEGY AT A MUSLIM CLOTHING STORE IN PADANGSIDIMPUAN CITY - Hery Dia Anata Batubara (SEAN Institute, 2022)
Indonesia is currently being hit by a problem, namely the problem of the Covid-19 pandemic. The huge impact arising from this pandemic is very much felt in various factors. From a health perspective, as of October 20, 2020, there were more than 290,000 confirmed cases of COVID-19. From an economic perspective, the COVID-19 pandemic has an impact on economic growth. Indonesia's economy in the first quarter of 2020 against the first quarter of 2019 was 2.97% (y-on-y), slowing down compared to the achievement in the first quarter of 2019 of 5.07%. (BPS Republic of Indonesia). In the production perspective, the number of production units decreased drastically due to the inability to maintain their production units which also had an impact on increasing the number of layoffs and unemployment, especially in production units in traditional markets which in fact have a slow economic growth rate coupled with the increasing number of competitors. This makes Indonesia in a dilemmatic position. Handling Problems to increase economic growth, the Indonesian government echoed the